1998
DOI: 10.1007/s002130050649
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortical involvement in phencyclidine-induced activation of the mesolimbic dopamine system: behavioral and neurochemical evidence

Abstract: Acute administration of phencyclidine to rats potently activates mesocorticolimbic dopaminergic neurons. The activation of dopamine release and utilization in the prefrontal cortex and nucleus accumbens are associated with profound cognitive impairment and hyperlocomotion, respectively. This dopaminergic activation by phencyclidine is not mediated by direct effects on the cell body regions of the dopamine neurons; however, phencyclidine augments dopamine release locally in the terminal fields. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 43 publications
9
43
1
Order By: Relevance
“…Phencyclidine and ketamine, noncompetitive antagonists at glutamate NMDA receptors, exacerbate positive and negative symptoms in schizophrenic patients, and induce schizophrenia-like symptoms and cognitive deficits in healthy volunteers (Javitt and Zukin, 1991;Krystal et al, 1994). This is in line with findings in rodents that intracortical or peripheral administration of NMDA receptor antagonists causes deficits in sensory-motor gating (Jentsch and Roth, 1999), hyperactivity (O'Neill and Liebman, 1987;Jentsch et al, 1998), and working memory (Wesierska et al, 1990;Verma and Moghaddam, 1996;Moghaddam et al, 1997;Aura and Riekkinen, 1999;Romanides et al, 1999). Peripherally administered phencyclidine or dizocilpine, noncompetitive NMDA receptor antagonists, or the selective NMDA-R2B receptor antagonist Ro 63-1908, cause deficits in attentional performance in a five-choice serial reaction time (5-CSRT) task Le Pen et al, 2003).…”
Section: Introductionsupporting
confidence: 86%
“…Phencyclidine and ketamine, noncompetitive antagonists at glutamate NMDA receptors, exacerbate positive and negative symptoms in schizophrenic patients, and induce schizophrenia-like symptoms and cognitive deficits in healthy volunteers (Javitt and Zukin, 1991;Krystal et al, 1994). This is in line with findings in rodents that intracortical or peripheral administration of NMDA receptor antagonists causes deficits in sensory-motor gating (Jentsch and Roth, 1999), hyperactivity (O'Neill and Liebman, 1987;Jentsch et al, 1998), and working memory (Wesierska et al, 1990;Verma and Moghaddam, 1996;Moghaddam et al, 1997;Aura and Riekkinen, 1999;Romanides et al, 1999). Peripherally administered phencyclidine or dizocilpine, noncompetitive NMDA receptor antagonists, or the selective NMDA-R2B receptor antagonist Ro 63-1908, cause deficits in attentional performance in a five-choice serial reaction time (5-CSRT) task Le Pen et al, 2003).…”
Section: Introductionsupporting
confidence: 86%
“…This finding is consistent with the results of both Druhan et al (1996) and Wolf et al (1994), who observed that MK-801 potentiated amphetamine-induced hyperactivity without, itself, inducing dopamine release in NAc or potentiating amphetamine-induced dopamine release. It has recently been suggested that locomotor effects of acutely administered PCP reflect its actions within PFC rather than NAc (Adams and Moghaddam, 1998;Jentsch et al, 1998b) which is consistent with an earlier work of Nabeshima et al (1983). The present study suggests that enhanced amphetamine-induced locomotor activity observed following chronic PCP treatment reflects the actions of PCP within PFC as well.…”
Section: Dissociation Between Behavioral Effects and Nac Dopamine Relsupporting
confidence: 92%
“…It is generally assumed that the rewarding effects of acute or chronic PCP treatment are related to an increase in mesolimbic extracellular dopaminergic levels (Di Chiara and Imperato, 1988;Carboni et al, 1989) and a dosedependent progressive downregulation of 5-HT 2A receptors in response to the elevation in serotonin turnover produced by the drug (Nabeshima et al, 1985(Nabeshima et al, , 1987Noda et al, 1998). Growing evidence indicates that PCP preferentially elevates dopaminergic transmission through its antagonist actions on NMDA receptors located on GABAegic inhibitory interneurons, thereby disinhibiting the firing of dopaminergic neurons, rather than through its action as a dopamine reuptake inhibitor (Jentsch et al, 1997a(Jentsch et al, , 1998a. Nonetheless, although PCP treatment seems to have a common stimulatory action on serotonergic and dopaminergic neurotransmission, cessation of drug administration (ie withdrawal) leads to different actions in the two systems.…”
Section: Discussionmentioning
confidence: 99%